THE GROWTH OF “ISLAMIC TOURISM” IN MAGHREB - Mauro Spotorno (Bollettino della Società Geografica Italiana, 2019)
Between 1995 and 2010 the tourist arrivals in Maghreb increased from 7 to 18 million with an average increase rate of 10.5% per year (the average world rate was 5%). Moreover, if in 1995 52% of visitors entering the Maghreb countries were Western, for the most part European, in 2010 the foreign tourists of islamic religion counted for 52%. However, in spite of its dimension, the phenomenon is quite marginal in the scientific tourist literature, so the aim of this study is to contribute to a better understanding of the reference mainframe. The tourist offer of the Maghreb countries has mostly followed a political and economic logic and met both the political and economic interest of the power elite and the needs of the tourist demand generated by the European and North-American centres of active tourism. However the new tourists of islamic religion bring values and requests deeply different from those which characterise the demand expressed by western tourism. A reply to these needs and to the consequent establishment of a specific market demand is given by the so called halal tourism that is the offer of services, social relationships and economic premises of the activities performed in accordance with the regulations of the Koran, the Sunna or more in general with the islamic tradition. The consolidation of this phenomenon brings about the problem of how to avoid forms of segregation corresponding to the manifestation of distinct if not opposite «worlds» in the tourism space.